Malignant Peripheral Nerve Sheath Tumor of the Small Bowel: An Unusual Presentation with Fatal Outcome. (28th August 2013) - Mohtaram, Amina; Mesmoudi, Siham; M'rabti, Hind; Rami, Amal; Latib, Rachida; Bernoussi, Zakia; Aaribi, Imane; Ben Ameur El Youbi, Meryam; Errihani, Hassan
Abstract : Malignant peripheral nerve sheath tumor of the small bowel is an extremely rare disease. Histologic distinction from other types of soft tissue sarcoma especially fibrosarcoma and leiomyosarcoma requires electron microscopy. Complete surgery remains the only curative treatment. However, late diagnosis makes curative surgery more difficult. The contribution of chemotherapy to incomplete surgery has been proved without controlled studies. We report a case of this type of lesion discovered following a small bowel perforation.